2012
DOI: 10.1016/j.ajpath.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-132 in Angiogenesis after Ocular Infection with Herpes Simplex Virus

Abstract: MicroRNAs (miRNAs) are small regulatory molecules that control diverse biological processes that include angiogenesis. Herpes simplex virus (HSV) causes a chronic immuno-inflammatory response in the eye that may result in corneal neovascularization during blinding immunopathological lesion stromal keratitis (SK). miR-132 is a highly conserved miRNA that is induced in endothelial cells in response to growth factors, such as vascular endothelial growth factor (VEGF). In this study, we show that miR-132 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 33 publications
1
84
0
1
Order By: Relevance
“…As a member of the miRNAs family, miR-132 plays an important role in inflammation, angiogenesis, and neural development [12][13][14]. Recent studies show that the dysregulation of miR-132 is related to a variety of human tumors, such as non-small cell lung cancer (NSCLC), osteosarcoma, breast cancer, hepatocellular carcinoma, prostate cancer, gastric cancer, and pancreatic cancer [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the miRNAs family, miR-132 plays an important role in inflammation, angiogenesis, and neural development [12][13][14]. Recent studies show that the dysregulation of miR-132 is related to a variety of human tumors, such as non-small cell lung cancer (NSCLC), osteosarcoma, breast cancer, hepatocellular carcinoma, prostate cancer, gastric cancer, and pancreatic cancer [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to accessibility of the lesion, there is greater potential for findings to be translated to medicine using local injection of microRNA intervention, limiting issues of systemic toxicity. 44 MicroRNAs have been implicated in the development of fibrosis via extracellular matrix and proliferative changes especially in liver, kidney and lung fibrotic diseases. 5,45,46 In this study, we aimed to ascertain the role of microRNAs in fibroblast function, using human pterygium as a model.…”
Section: Introductionmentioning
confidence: 99%
“…How miR-132 promotes angiogenesis during HSK simultaneously by degrading angiogenic MMP-9 needs further investigation. 12,43 However, miR-132 blockadeinduced reduction in CV and expression of miR-132 in blood vessel endothelial cells while MMP-9 in neutrophils make MMP-9 an unlikely target of miR-132 during HSK.…”
Section: Mirnas and Angiogenesismentioning
confidence: 99%
“…34 We have also shown that miR-132 is also upregulated in animals with CV following HSV infection. 12 In the HSV system, the upregulation of miR-132 may be in part the consequence of stimulation by an as-yetunidentified mechanism by IL-17, a cytokine produced early in HSK pathogenesis by gamma delta cells of the innate immune system. 35 The upregulated miR-132 appears to act to augment VEGF signaling via an inhibitory effect on a negative regulator of VEGF function, Ras-GAP.…”
Section: Mirnas and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation